Deradicalization of Religious Behavior Through Character Building of Islamic Unity Students with Bai'at System and Embodiment of Pancasila Values - Beni Ahmad Saebani; Yana Sutiana; Muhammad Ilham Pratama; Adilla Nur Muslimah (Dinasti Research, 2025)
The Islamic religious organization Persatuan Islam was founded on September 12, 1923 in Bandung. Now the Islamic Association has approximately 230 boarding schools throughout Indonesia. The number is not small with a management system that has been tested, it is proven that the longer the Islamic Unity boarding school is growing rapidly with santri alumni spread throughout Indonesia. However, there is something interesting about this Islamic Unity Islamic Boarding School, namely the implementation of the santri promise which is read every day of the week in the santri ceremony. This promise aims to shape the morals of students and most importantly to prevent behavior that deviates from Islamic law. This study aims to analyze the material of the Islamic Unity boarding school's santri pledge so that it can ward off radical behavior in religion and form the character of santri and embody the values of Pancasila. The research was conducted at Islamic Unity boarding schools in Bangil, East Java, West Java, and those in Central Java. The method used is descriptive analytical with a sociological and philosophical approach. Data were collected by observation, interview, and documentation. The data obtained were classified and analyzed using the content analysis method. The concept of de-radicalization of religious behavior and character building of santri through the santri promise system in Islamic Unity boarding schools in Indonesia refers to the vision of PERSIS pesantren education, namely realizing santri and pesantren alumni who have a deep understanding of Islamic teachings, have good character, and become role models for the people. Deradicalization will automatically be implemented because the santri uphold their promises. The embodiment of Pancasila values through the santri pledge system in Islamic Unity boarding schools in Indonesia is carried out through Muslim character education that is faithful, pious, instills a spirit of togetherness, tolerance, rational, emotional and spiritual intelligence. The realization is in the form of skills training, curriculum, and cultivating various obligations and sunnat-sunnat in Islamic teachings.